Staphylococcus aureus adaptive evolution: Recent insights on how immune evasion, immunometabolic subversion and host genetics impact vaccine development - Wong Fok Lung, Tania; Chan, Liana C.; Prince, Alice; Yeaman, Michael R.; Archer, Nathan K.; Aman, M. Javad; Proctor, Richard A. (Frontiers in Cellular and Infection Microbiology, 2022)
Despite meritorious attempts, a S. aureus vaccine that prevents infection or mitigates severity has not yet achieved efficacy endpoints in prospective, randomized clinical trials. This experience underscores the complexity of host-S. aureus interactions, which appear to be greater than many other bacterial pathogens against which successful vaccines have been developed. It is increasingly evident that S. aureus employs strategic countermeasures to evade or exploit human immune responses. From entering host cells to persist in stealthy intracellular reservoirs, to sensing the environmental milieu and leveraging bacterial or host metabolic products to reprogram host immune responses, S. aureus poses considerable challenges for the development of effective vaccines. The fact that this pathogen causes distinct types of infections and can undergo transient genetic, transcriptional or metabolic adaptations in vivo that do not occur in vitro compounds challenges in vaccine development. Notably, the metabolic versatility of both bacterial and host immune cells as they compete for available substrates within specific tissues inevitably impacts the variable repertoire of gene products that may or may not be vaccine antigens. In this respect, S. aureus has chameleon phenotypes that have alluded vaccine strategies thus far. Nonetheless, a number of recent studies have also revealed important new insights into pathogenesis vulnerabilities of S. aureus. A more detailed understanding of host protective immune defenses versus S. aureus adaptive immune evasion mechanisms may offer breakthroughs in the development of effective vaccines, but at present this goal remains a very high bar. Coupled with the recent advances in human genetics and epigenetics, newer vaccine technologies may enable such a goal. If so, future vaccines that protect against or mitigate the severity of S. aureus infections are likely to emerge at the intersection of precision and personalized medicine. For now, the development of S. aureus vaccines or alternative therapies that reduce mortality and morbidity must continue to be pursued.